P2X7 siRNA targeted to the kidneys increases klotho and delays the progression of experimental diabetic nephropathy - Rodrigues, A. M. (Purinergic Signal, 2020)
Previous studies in our laboratory have suggested that P2X7 could contribute to the progression of diabetic nephropathy and modulated klotho expression. The aim of this study was to investigate if P2X7 receptor is related to the expression of klotho in the onset of diabetic nephropathy in rats. Seven-week-old male Wistar rats weighing 210 g were all uninephrectomized; two-third of the animals were induced to diabetes with 60 mg/kg streptozotocin i.v., and one-third received its vehicle (control rats). At 4th day of the fifth week of the protocol, half of the diabetic rats received a small interfering RNA targeting for P2X7 mRNA, and the other half received its vehicle. Euthanasia was made at the eighth week. Diabetic animals reproduced all classic symptoms of the disease; besides, they showed reduced renal function and low NO bioavailability; also, SOD1, SOD2, and catalase were increased, probably due to the oxidative stress which was elevated in this situation. Metabolic data of diabetic rats did not change by silencing P2X7 receptor. For the other hand, silencing P2X7 was able to contribute to balance oxidative and nitrosative profile, ultimately improving the renal function and increasing plasma and membrane forms of klotho. These findings suggest that the management of P2X7 receptor can benefit the kidneys with diabetic nephropathy. Further studies are needed to show the therapeutic potential of this receptor inhibition to provide a better quality of life for the diabetic patient. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11302-020-09695-1) contains supplementary material, which is available to authorized users.